Self-reported symptoms of depression and anxiety among informal caregivers of persons with dementia: a cross-sectional comparative study between Sweden and Italy - Joseba Wulff; Agneta Malmgren Fänge; Connie Lethin; Carlos Chiatti (BMC, 2020)
Abstract Background Around 50 million people worldwide are diagnosed with dementia and this number is due to triple by 2050. The majority of persons with dementia receive care and support from their family, friends or neighbours, who are generally known as informal caregivers. These might experience symptoms of depression and anxiety as a consequence of caregiving activities. Due to the different welfare system across European countries, this study aimed to investigate factors associated with self-reported depression and anxiety among informal dementia caregivers both in Sweden and Italy, to ultimately improve their health and well-being. Methods This comparative cross-sectional study used baseline data from the Italian UP-TECH (n = 317) and the Swedish TECH@HOME (n = 89) studies. Main outcome variables were the severity of self-reported anxiety and depression symptoms, as measured by the Hospital Anxiety and Depression Scale (HADS). HADS scores were investigated using descriptive and bivariate statistics to compare means and standard deviations. Linear regressions were used to test for associations between potential factors and self-reported symptoms of depression and anxiety. Results Italian informal caregivers reported more severe symptoms of depression and anxiety than Swedish caregivers. In Italy, a higher number of hours of caregiving was associated with anxiety symptoms (β = − 1.205; p = 0.029), being 40-54 years-old with depression symptoms (β = − 1.739; p = 0.003), and being female with symptoms of both depression (β = − 1.793; p < 0.001) and anxiety (β = 1.474; p = 0.005). In Sweden, a higher number of hours of caregiving and being < 39 years-old were associated with depression symptoms (β = 0.286; p < 0.000; β = 3.945; p = 0.014) and a higher number of hours of caregiving, the lack of additional informal caregivers and dementia severity were associated with anxiety symptoms (β = 0.164; p = 0.010; β = − 1.133; p = 0.033; β = − 1.181; p = 0.031). Conclusion Multiple factors are associated with self-reported symptoms of depression and anxiety among informal caregivers in Sweden and Italy. Factors found in this study partly differ between the two countries, suggesting the important role of cultural and social factors affecting the experience of caregiving. A deeper knowledge of these factors may increase the knowledge on potential protective and risk factors, provide information to policymakers and ultimately improve the psychological well-being of informal caregivers to people with dementia across Europe.